2017
DOI: 10.1017/s0022377817000630
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar wind nebulae created by fast-moving pulsars

Abstract: We review multiwavelength properties of pulsar wind nebulae created by supersonically moving pulsars and the effects of pulsar motion on the pulsar wind nebulae morphologies and the ambient medium. Supersonic pulsar wind nebulae are characterized by bow-shaped shocks around the pulsar and/or cometary tails filled with the shocked pulsar wind. In the past several years significant advances in supersonic pulsar wind nebula studies have been made in deep observations with the Chandra and XMM-Newton X-ray observat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 94 publications
7
107
0
Order By: Relevance
“…Note that Kargaltsev et al (2017) suggested another geometry of the system, which is shown in the bottom panel of Fig. 6 (see also their fig.…”
Section: Pwnmentioning
confidence: 86%
See 1 more Smart Citation
“…Note that Kargaltsev et al (2017) suggested another geometry of the system, which is shown in the bottom panel of Fig. 6 (see also their fig.…”
Section: Pwnmentioning
confidence: 86%
“…Studies of the latter objects, in turn, provide additional information about pulsar parameters (e.g. ages, distances, proper motions, geometries) and interaction of relativistic pulsar winds with the ambient medium (e.g., Gaensler & Slane 2006;Kargaltsev et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is another interpretation of 'lateral tails' as jets or an equatorial torus bent back by the ram pressure [6,7,8]. We show possible geometries in figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Consider a pulsar with spindown powerĖ moving with velocity vp through a medium of particle density n (see e.g. Kargaltsev et al 2017, for review). The stand-off distance is…”
Section: Length and Brightness Estimatesmentioning
confidence: 99%